ANALISIS FAKTOR-FAKTOR YANG BERPENGARUH PADA PEMILIHAN METODE DEPRESIASI - Rossje V. Suryaputri; Kerna la Wardhany (LEMBAGA PENERBIT FAKULTAS EKONOMI DAN BISNIS UNIVERSITAS TRISAKTI, 2004)
The main objective ofthis study is to obtain evidence whether manager choices to depreciation methods, is related and affected by firm's size, leverage ratio, and account-ing ROA. It' is assumed that manager in the small company with high leverage ratio, and decreasing trend of accounting ROA preferred to select depreciation method which can increase the reported earning by using the straight-line depreciation method. On the contrary, manager in the larger company with low leverage ratio and increasing trend of accounting ROA tend to select depreciation method which can reduce the repotted earning by using double declining balance or accebrated depreciation method.This study was conducted byselecting of 129 publiclisted manufacturing compa-nies. The firm's size was detennined by total assets, while leverage ratio and accounting ROA were measured by the ratio of total liabilities to total assets and ratio of operating pinfit to average of total assets. The study concludes that there was a positive correlation between leverage ratio and the choice of depreciation method. On the contrary, there was no correlation between the firm's size and accounting ROA with the choice of depreciation method. There was an effect of leverage ratio to the selection of depreciation method. On the other hand, there was no effect between the firm's size and accounting ROA to the selection of depreciation methodKeywords: Depreciation method, firm size, leverage, ROA